Diel Vertical Distribution of Mesozooplankton Functional Groups in the North Pacific Subtropical Gyre: A Case Study - Ge, Ruping; Li, Yixuan; Chen, Hongju; Lei, Facan; Zhuang, Yunyun; Liu, Guangxing (Frontiers in Marine Science, 2022)
Understanding the diel vertical migration (DVM) patterns of zooplankton has important implications for biological pumping and pelagic food webs. The functional traits of zooplankton generally determine their distribution in the environment. However, knowledge about the DVM patterns of zooplankton with different functional traits is limited. Here, we used a trait-based approach to study the vertical distributions of zooplankton in the North Pacific Subtropical Gyre (NPSG). Four functional traits, namely, body length, feeding type, trophic group, and reproductive mode, were selected in this study. A high biodiversity of zooplankton (165 taxa) was recorded in the NPSG. Zooplankton was mainly concentrated above 100 m and exhibited normal DVM. Zooplankton with small and medium body sizes (<2 mm, 69% ± 16%), current feeding (43% ± 14%), and omnivore–herbivores (54% ± 14%) were dominant in the NPSG. The proportion of sac spawners in total abundance (52% ± 14%) was higher than that of broadcast spawners (48% ± 14%), which differed from that in the coastal regions. Sixteen functional groups of zooplankton were identified. Different functional groups exhibited distinct DVM patterns due to the influence of different factors. The DVM patterns of current-feeding omnivore–herbivores were significantly correlated with chlorophyll a, whereas giant ambush-feeding carnivores exhibited normal DVM patterns and were substantially correlated with the vertical distribution of their food organisms. However, the small omnivore–carnivores showed reverse DVM patterns. Overall, this study provided a new perspective for studies on zooplankton DVM from the aspect of functional traits.